Measuring Effectiveness in Nonprofit Organizations: An Integration Effort - TAYŞİR, EYÜP AYGÜN (My University, 2012)
In this study, we aimed to reveal the multidimensional structure of NPO effectiveness by compiling the different effectiveness dimensions that were used by NPO effectiveness researchers. After compiling these dimensions, we conducted research to analyze the extent to which the literature represents the social reality. In order to do that, we collected data from 69 leading Turkish NPOs. The results showed that almost every dimension that had earlier been mentioned in the literature had a capacity to represent one aspect of NPO effectiveness, which is why the integration is a prerequisite. Thus, we suggested an evaluation model which comprises the main and sub-dimensions of NPO effectiveness and the indicators of these dimensions. © 2012 Copyright Taylor and Francis Group, LLC.
Keywords: effectiveness; effectiveness measurement model; nonprofit organizations